The Yponomeutidae of the Afrotropical region (Lepidoptera: Yponomeutoidea) - Agassiz, David J. L. (Zootaxa, 2019)
The Yponomeutidae of the Afrotropical region are revised. The generic name Trisophista Meyrick is restored, stat. rev. Three new synonymies are established: Trisophista pauli Viette, 1967 is a junior synonym of Yponomeuta strigillata Zeller,1852 syn. nov., Yponomeuta parvipunctus Gershenson & Ulenberg, 1998 is a junior synonym of Y. sistrophora Meyrick, 1909, and Paraswammerdamia malgasella Viette, 1954 is a junior synonym of Yponomeuta subplumbella Walsingham, 1881, syn. nov. A new genus Dukeia is described. 21 new species are described: Cedestis nathani, Kessleria africana, Swammerdamia tobii, Xyrosaris louisae, X. lucae, Yponomeuta alexi, Y. atricatoa, Y. capensis, Y. dhofarensis, Y. gnophera, Y. griseomacula, Y. ioni, Y, malagasella, Y. melanephos, Y. nephella, Y. onyxella, Y. orocola, Y. oromiensis, Y. staudei, Y. superplumbella and Y. zambesica.